How can clinical research improve European health outcomes in cancer?. (June 2019) - Selby, Peter; Liu, Lifang; Downing, Amy; Banks, Ian; Wilson, Roger; Stephens, Richard; Meunier, Francoise; Rochon, Justine; Morris, Eva; Seymour, Matt; Gregory, Walter; Lawler, Mark; et al.
Highlights: Clinical cancer research is core activity for cancer professionals. It is strongly supported by cancer patients. Modern health informatics allows us to measure its impact in very large datasets. Evidence from positive clinical trials improves care and is cost effective. Participation in clinical trials probably also improves care and saves lives. Abstract: We review the mechanisms by which clinical cancer research can improve health outcomes and argue that this should be central to the development of policy. Recent series of major international studies have analysed large, often nationwide, datasets for cancer patient outcomes and participation in clinical research. They have evaluated and quantified the impact of new evidence generated by randomised controlled trials on cancer survival. They show a strong and probably causal relationship between the participation in clinical research in hospitals and the outcomes for patients with the disease under study in those hospitals. Also, institutions that are active in clinical trials appear to take up well evidenced innovations more rapidly than those which are not so engaged. Further work is necessary to confirm and examine the generalisability of these findings but we argue that all of these mechanisms are likely to lead to improved outcomes for patients as a consequence of the conduct of clinical research. The size of the benefit appears to be substantial and an active programme to promote clinical research across cancer care systems should be a part of National Cancer Plans and Cancer Control Strategies.